Measurement of the production and elliptic flow of (anti)nuclei in Xe-Xe collisions at √sNN=5.44$ TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Menzel, Marius; et al. (Physical review, 2024)
Measurements of (anti)deuteron and (anti)3He production in the rapidity range |𝑦|<0.5 as a function of the transverse momentum and event multiplicity in Xe-Xe collisions at a center-of-mass energy per nucleon-nucleon pair of √𝑠𝑁⁢𝑁=5.44 TeV are presented. The coalescence parameters 𝐵2 and 𝐵3 are measured as a function of the transverse momentum per nucleon. The ratios between (anti)deuteron and (anti)3He yields and those of (anti)protons and pions are reported as a function of the mean charged-particle multiplicity density and compared with two implementations of the statistical hadronization model and with coalescence predictions. The elliptic flow of (anti)deuterons is measured for the first time in Xe-Xe collisions and shows features similar to those already observed in Pb-Pb collisions, i.e., the mass ordering at low transverse momentum and the meson-baryon grouping at intermediate transverse momentum. The production of nuclei is particularly sensitive to the chemical freeze-out temperature of the system created in the collision, which is extracted from a grand-canonical-ensemble-based thermal fit, performed for the first time including light nuclei along with light-flavor hadrons in Xe-Xe collisions. The extracted chemical freeze-out temperature 𝑇chem=(154.2±1.1) MeV in Xe-Xe collisions is similar to that observed in Pb-Pb collisions and close to the crossover temperature predicted by lattice quantum chromodynamics calculations.